The Effect of Prenatal Yoga and the Administration of Pepermint Aromatherapy in Reducing III Trimester Discomfort in Pregnant Women at the Walantaka Health Center in Serang City HIV and AIDS - Ferawati Ferawati; Rahayu Khairiah (STIKep PPNI Jawa Barat, 2023)
Aims: To determine the effect of prenatal yoga and administration of peppermint aromatherapy in reducing third trimester discomfort in pregnant women at the Walantaka Public Health Center, Serang City Methods: This quasi-experimental design study used a one group pretest-posttest design approach. Samples were collected using quota sampling totaling 36 pregnant women in the third trimester. Results: The average before giving prenatal yoga and giving peppermint aromatherapy third trimester discomfort to pregnant women was 10.33 and the average after being given prenatal yoga and giving peppermint aromatherapy third trimester discomfort to pregnant women was reduced by 7.53. Conclusion: The effect of prenatal yoga and administration of peppermint aromatherapy in reducing third trimester discomfort in pregnant women at the Walantaka Public Health Center Serang City (p.value 0.000). It is hoped that the results of this study can be used as information material to be conveyed to pregnant women patients to be able to do prenatal yoga and give peppermint aromatherapy in reducing the discomfort of the third trimester.